PSYCHOLOGICAL SAFETY ENSURING SYSTEM OF PERSONALITY IN UNFAVOURABLE LIVING CIRCUMSTANCES - MKRTUMYAN, MELS; MKRTUMYAN, LILIT (Main Issues Of Pedagogy And Psychology, 2018)
The article discusses the changes of the psycho-physiological pecularities of psychological safety system of human activity in unfavourable socio-civil, economical development circumstances of the 21-st century. The pecularities of the changes in negative psychological states, as well as the functional capabilities of a person in unfavourable living circumstances are revealed. The article offers a system for organising psychological work. The mastery of the latter ensures high reliability of person’s general and mental health in different life situations.